Geomorphometric analysis of Zimbabwe’ digital elevation model and issues of exogenic metallogeny - P. A. Ignatov; E. V. Polyakova; A. L. Mineev; S. A. Malyutin (Известия высших учебных заведений: Геология и разведка, 2025)
Background. The raw material base of the Republic of Zimbabwe covers numerous endogenic deposits of chromium, nickel, copper, platinum, gold, diamonds, and other minerals. Exogenic deposits are of less occurrence. Most exogenic nickel deposits in the weathering crust and gold ore placers have reached their point of exhaustion. However, there remain prospects for discovering new objects, which determines the relevance of forecasting and prospecting of hidden exogenic deposits in Zimbabwe.Aim. A geomorphometric analysis of a digital elevation model (DEM) of Zimbabwe with a view to forecasting and prospecting exogenic mineral deposits.Materials and methods. A digital elevation model (DEM) of the Republic of Zimbabwe was constructed using 120 scenes of the SRTM Void Filled global DEM (SRTM (Shuttle Radar Topography Mission) version with filled areas of missing data) with a spatial resolution of 3 arcseconds (~90 meters per pixel). The data was obtained through the EarthExplorer service (https://earthexplorer.usgs.gov) from the USGS (US Geological Survey). All operations were performed in the open-access SAGA GIS software (http://www.saga-gis.org).Results. Prospects for discovering exogenic deposits formed in the Neogene-Quaternary period can be assessed by calculating the geomorphometric parameters of the terrain. The conducted analysis of the DEM of Zimbabwe established that its terrain contains the following regional elements of the geological structure: outcrops of the Archean basement, the Great Dyke, Proterozoic formations of the folded framework of the basement, rocks of the Mesozoic and Cenozoic cover. Large terrain segments contain metallogenic taxa, including the Zimbabwean Archean endogenic ore belt. The main watershed divides the area into two geomorphologically different — north-western and south-eastern — parts.Conclusion. Large terrain segments of the area under study are shown to contain metallogenic taxa, including the Zimbabwean Archean ore belt. An assumption is made that buried placers of gold and platinum, as well as redeposited deposits of cobalt, nickel, and scandium in the lateritic weathering crust should be widespread northwest of the main watershed.